What if my coworker builds a better LMX? The roles of envy and coworker pride for the relationships of LMX social comparison with learning and undermining. (10th August 2021) - Pan, Jingzhou; Zheng, Xiaotong (Janey); Xu, Haoying (Howie); Li, Jie (Kassie); Lam, Catherine K.
Summary: Although the extant literature has demonstrated the benefits of building a higher leader–member exchange (LMX) relationship with a leader, it has overlooked the efforts by lower LMX employees to leverage the difference from higher LMX coworkers. Integrating social comparison theory and EASI theory, we contend that lower LMX social comparison (LMXSC) is associated with positive (self‐improving) and negative (undermining) behavior via different emotional mechanisms and that the focal employee's perceptions of the comparison coworker's pride play a critical role in qualifying the effects of lower LMXSC. The results from a time‐lagged field study and an online experiment reveal that lower LMXSC is associated with both benign and malicious envy, which in turn respectively relate to the focal employee learning and socially undermining the superior coworker. The negative indirect effect of LMXSC on learning behaviors via benign envy is stronger when the coworker compared is perceived to be higher (vs. lower) in authentic pride, whereas the indirect effect of LMXSC on social undermining via malicious envy is stronger when the coworker compared is perceived to be higher (vs. lower) in hubristic pride. We conclude with theoretical and practical implications.